Combine.

Combine.

Move <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> by <math><mstyle displaystyle="true"><msup><mrow><mi>x</mi></mrow><mrow><mn>3</mn></mrow></msup></mstyle></math> .

Raise <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> to the power of <math><mstyle displaystyle="true"><mn>1</mn></mstyle></math> .

Use the power rule <math><mstyle displaystyle="true"><msup><mrow><mi>a</mi></mrow><mrow><mi>m</mi></mrow></msup><msup><mrow><mi>a</mi></mrow><mrow><mi>n</mi></mrow></msup><mo>=</mo><msup><mrow><mi>a</mi></mrow><mrow><mi>m</mi><mo>+</mo><mi>n</mi></mrow></msup></mstyle></math> to combine exponents.

Add <math><mstyle displaystyle="true"><mn>1</mn></mstyle></math> and <math><mstyle displaystyle="true"><mn>3</mn></mstyle></math> .

Move <math><mstyle displaystyle="true"><msup><mrow><mi>y</mi></mrow><mrow><mn>2</mn></mrow></msup></mstyle></math> .

Add <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> and <math><mstyle displaystyle="true"><mn>3</mn></mstyle></math> .

Cancel the common factor of <math><mstyle displaystyle="true"><mn>6</mn></mstyle></math> and <math><mstyle displaystyle="true"><mn>15</mn></mstyle></math> .

Factor <math><mstyle displaystyle="true"><mn>3</mn></mstyle></math> out of <math><mstyle displaystyle="true"><mn>6</mn><msup><mrow><mi>x</mi></mrow><mrow><mn>4</mn></mrow></msup><mo>⋅</mo><mn>14</mn><mrow><mo>(</mo><mn>25</mn><msup><mrow><mi>y</mi></mrow><mrow><mn>4</mn></mrow></msup><mo>)</mo></mrow></mstyle></math> .

Cancel the common factors.

Factor <math><mstyle displaystyle="true"><mn>3</mn></mstyle></math> out of <math><mstyle displaystyle="true"><mn>7</mn><msup><mrow><mi>y</mi></mrow><mrow><mn>5</mn></mrow></msup><mo>⋅</mo><mn>15</mn><msup><mrow><mi>x</mi></mrow><mrow><mn>3</mn></mrow></msup></mstyle></math> .

Cancel the common factor.

Rewrite the expression.

Cancel the common factor of <math><mstyle displaystyle="true"><msup><mrow><mi>x</mi></mrow><mrow><mn>4</mn></mrow></msup></mstyle></math> and <math><mstyle displaystyle="true"><msup><mrow><mi>x</mi></mrow><mrow><mn>3</mn></mrow></msup></mstyle></math> .

Factor <math><mstyle displaystyle="true"><msup><mrow><mi>x</mi></mrow><mrow><mn>3</mn></mrow></msup></mstyle></math> out of <math><mstyle displaystyle="true"><mn>2</mn><msup><mrow><mi>x</mi></mrow><mrow><mn>4</mn></mrow></msup><mo>⋅</mo><mn>14</mn><mrow><mo>(</mo><mn>25</mn><msup><mrow><mi>y</mi></mrow><mrow><mn>4</mn></mrow></msup><mo>)</mo></mrow></mstyle></math> .

Cancel the common factors.

Factor <math><mstyle displaystyle="true"><msup><mrow><mi>x</mi></mrow><mrow><mn>3</mn></mrow></msup></mstyle></math> out of <math><mstyle displaystyle="true"><mn>7</mn><msup><mrow><mi>y</mi></mrow><mrow><mn>5</mn></mrow></msup><mo>⋅</mo><mn>5</mn><msup><mrow><mi>x</mi></mrow><mrow><mn>3</mn></mrow></msup></mstyle></math> .

Cancel the common factor.

Rewrite the expression.

Cancel the common factor of <math><mstyle displaystyle="true"><mn>14</mn></mstyle></math> and <math><mstyle displaystyle="true"><mn>7</mn></mstyle></math> .

Factor <math><mstyle displaystyle="true"><mn>7</mn></mstyle></math> out of <math><mstyle displaystyle="true"><mn>2</mn><mi>x</mi><mo>⋅</mo><mn>14</mn><mrow><mo>(</mo><mn>25</mn><msup><mrow><mi>y</mi></mrow><mrow><mn>4</mn></mrow></msup><mo>)</mo></mrow></mstyle></math> .

Cancel the common factors.

Factor <math><mstyle displaystyle="true"><mn>7</mn></mstyle></math> out of <math><mstyle displaystyle="true"><mn>7</mn><msup><mrow><mi>y</mi></mrow><mrow><mn>5</mn></mrow></msup><mo>⋅</mo><mn>5</mn></mstyle></math> .

Cancel the common factor.

Rewrite the expression.

Cancel the common factor of <math><mstyle displaystyle="true"><mn>25</mn></mstyle></math> and <math><mstyle displaystyle="true"><mn>5</mn></mstyle></math> .

Factor <math><mstyle displaystyle="true"><mn>5</mn></mstyle></math> out of <math><mstyle displaystyle="true"><mn>2</mn><mi>x</mi><mo>⋅</mo><mn>2</mn><mrow><mo>(</mo><mn>25</mn><msup><mrow><mi>y</mi></mrow><mrow><mn>4</mn></mrow></msup><mo>)</mo></mrow></mstyle></math> .

Cancel the common factors.

Factor <math><mstyle displaystyle="true"><mn>5</mn></mstyle></math> out of <math><mstyle displaystyle="true"><msup><mrow><mi>y</mi></mrow><mrow><mn>5</mn></mrow></msup><mo>⋅</mo><mn>5</mn></mstyle></math> .

Cancel the common factor.

Rewrite the expression.

Cancel the common factor of <math><mstyle displaystyle="true"><msup><mrow><mi>y</mi></mrow><mrow><mn>4</mn></mrow></msup></mstyle></math> and <math><mstyle displaystyle="true"><msup><mrow><mi>y</mi></mrow><mrow><mn>5</mn></mrow></msup></mstyle></math> .

Factor <math><mstyle displaystyle="true"><msup><mrow><mi>y</mi></mrow><mrow><mn>4</mn></mrow></msup></mstyle></math> out of <math><mstyle displaystyle="true"><mn>2</mn><mi>x</mi><mo>⋅</mo><mn>2</mn><mrow><mo>(</mo><mn>5</mn><msup><mrow><mi>y</mi></mrow><mrow><mn>4</mn></mrow></msup><mo>)</mo></mrow></mstyle></math> .

Cancel the common factors.

Factor <math><mstyle displaystyle="true"><msup><mrow><mi>y</mi></mrow><mrow><mn>4</mn></mrow></msup></mstyle></math> out of <math><mstyle displaystyle="true"><msup><mrow><mi>y</mi></mrow><mrow><mn>5</mn></mrow></msup></mstyle></math> .

Cancel the common factor.

Rewrite the expression.

Multiply <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mn>5</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>4</mn></mstyle></math> .

Do you know how to Simplify (6x^3)/(7y^3)*(14x)/(15y^2)*(25y^4)/(x^3)? If not, you can write to our math experts in our application. The best solution for your task you can find above on this page.